The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.6007/ijarbss/v6-i11/2396
|View full text |Cite
|
Sign up to set email alerts
|

School Culture and Its Relationship with Teacher Leadership

Abstract: This study aimed to investigate the relationship between school culture and teacher leadership. A total of 194 teachers from 22 primary schools were selected as respondents. A set of questionnaires were used as primary data collection and the data were analysed using descriptive statistics. The findings show that "teachers' professionalism and goal setting" is the dominant school culture dimensions. Whereas, "exemplify the best" and "being referenced leader" are the widely practiced teacher leadership features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
(12 reference statements)
2
9
0
2
Order By: Relevance
“…Similar findings are also reported in other studies (Kabler, 2013;Öztürk, 2015;Yusof, Osman, & Noor, 2016). Accordingly, it can be said that teacher leadership behaviors in high schools increase in parallel with task-oriented, success-oriented, bureaucratic, and support-oriented culture.…”
Section: Discussion Results and Suggestionssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings are also reported in other studies (Kabler, 2013;Öztürk, 2015;Yusof, Osman, & Noor, 2016). Accordingly, it can be said that teacher leadership behaviors in high schools increase in parallel with task-oriented, success-oriented, bureaucratic, and support-oriented culture.…”
Section: Discussion Results and Suggestionssupporting
confidence: 89%
“…In this way, the findings obtained in the present study can provide important insights to practitioners and policymakers regarding the characteristics of school culture that enable teachers to perform leadership behaviors at a higher level. On the other hand, previous studies examining the relationship between school culture and teacher leadership are limited in number (Kabler, 2013;Öztürk, 2015;Yusof, Osman, & Noor, 2016). Furthermore, in his analysis that examined 52 papers, Poekert (2012) reported that studies mostly focused on the characteristics of teacher leadership, and those related to the development of teacher leadership were still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Budaya sekolah dan motivasi kerja baik secara parsial maupun simultan berpengaruh terhadap kinerja guru. Keterampilan memimpinan juga merupakan salah satu kinerja guru yang dapat dipengaruhi oleh budaya sekolah (Yusof et al, 2016).…”
Section: 37unclassified
“…When teacher leadership is developed, it not only fosters improved teaching efficiency, but it promotes educational practice outside the classroom (Katzenmeyer & Moller, 2009;York-Barr & Duke, 2004), which is an important factor in advancing school education and teaching reform. A school's organizational culture is one of the many factors that affect the leadership of university teachers (Lesinger et al, 2016;Mangin, 2005;Öztürk & Şahin, 2020;Theingi & Ye, 2022;Yusof et al, 2016). Cansoy and Parlar (2017) and Kara (2022) explored the relationship between different organizational cultures in schools and teacher leadership, finding that support-oriented culture, success-oriented culture, task-oriented culture, and bureaucratic culture all have significant impacts on teacher leadership.…”
Section: Introductionmentioning
confidence: 99%